2005
DOI: 10.1007/s11178-005-0222-y
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Addition to Acetylenes in Superbasic Catalytic Systems: XIII. Fluoride Cesium Containing Systems, Efficient Catalysts for Alkanols Vinylation

Abstract: New catalytic systems CsFMOH (M = Li, Na) were developed for the synthesis of alkyl vinyl ethers comparable in efficiency to cesium alcoholates. The addition of primary and secondary alcohols to acetylene occurs in the presence of these systems at the atmospheric (DMSO, 100°C) or at enhanced (without solvent, 135 140°C) acetylene pressure and affords alkyl vinyl ethers in up to 93% yield. * For communication XII see [1]. The systematic investigation of alcohols vinylation with acetylenes discovered by A.E. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A series of experiments was conducted with water/DMSO mixture as a solvent ( Table 1, entries 4-6). This option was stimulated by previous investigations both experimental 5,8,[38][39][40] and theoretical [40][41][42][43] proving that the superbasic media like KOH/DMSO(water) actively catalyse the nucleophilic additions to acetylenes. In particular, it was shown that in the KOH/DMSO catalytic media, methanol was smoothly vinylated with acetylene gas at 80-120 ∘ C and atmospheric pressure.…”
Section: Resultsmentioning
confidence: 99%
“…A series of experiments was conducted with water/DMSO mixture as a solvent ( Table 1, entries 4-6). This option was stimulated by previous investigations both experimental 5,8,[38][39][40] and theoretical [40][41][42][43] proving that the superbasic media like KOH/DMSO(water) actively catalyse the nucleophilic additions to acetylenes. In particular, it was shown that in the KOH/DMSO catalytic media, methanol was smoothly vinylated with acetylene gas at 80-120 ∘ C and atmospheric pressure.…”
Section: Resultsmentioning
confidence: 99%
“…1,4-Dioxane and Et 2 O were dried and freshly distilled from metallic Na before use. Vinyl ethers 1a-c, 15 1d,e, 16 1f, 17 and 1k 18 were prepared according to the published methods. Vinyl ethers 1g-i and the 1,4-bis(vinyloxy)benzene were synthesized by direct vinylation of the corresponding phenol or hydroquinone with acetylene in KOH-DMSO suspension (unpublished data).…”
Section: Scheme 1 Synthesis Of Bisphosphinodiselenoic Ester 3pmentioning
confidence: 99%
“…2, curve 3). Under comparable conditions [1] the yield of vinyl heptyl ether obtained by vinylation of 1-heptanol was 87%.…”
mentioning
confidence: 91%
“…Therefore the search for new catalysts for the efficient and selective synthesis of mono-and divinyl ethers from diols remains an urgent problem. With this goal we have for the first time studied a reaction of acetylene with diols in the presence of a new catalytic system CsFNaOH [1,14] whose efficiency is due apparently mainly to the formation in situ of anhydrous cesium hydroxide nanoparticles. The an-hydrous cesium hydroxide is known to be more active [15] but less available than KOH vinylation catalyst.…”
mentioning
confidence: 99%
See 1 more Smart Citation